1986
DOI: 10.1093/nar/14.6.2413
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and expression of cDNA encoding mouse tyrosinase

Abstract: We have isolated a pigment cell-specific cDNA clone from a B16 mouse melanoma cDNA library by differential hybridization. The mRNA of isolated cDNA is highly expressed in B16 melanoma cells and in black mouse (C57BL/6) skin, but is not detectable in mouse neuroblastoma cells nor in K1735 mouse amelanotic melanoma cells. The protein sequence deduced from the nucleotide sequence of the cloned cDNA shows significant similarity to the entire region of Neurospora tyrosinase. To know the identity of cDNA, we transfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
144
2
1

Year Published

1988
1988
2006
2006

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 240 publications
(147 citation statements)
references
References 47 publications
0
144
2
1
Order By: Relevance
“…2. There was 90% identity with amino acid sequences deduced from the mouse cDNA clone, pMT4, isolated by Shibahara et al (at amino acid positions 247-260, 333-349, and 428-441 ofpMT4) (15). Oligonucleotide probes were derived from peptide sequences of p75 and used to screen a cDNA library constructed from the human melanoma cell line SK-MEL-19.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2. There was 90% identity with amino acid sequences deduced from the mouse cDNA clone, pMT4, isolated by Shibahara et al (at amino acid positions 247-260, 333-349, and 428-441 ofpMT4) (15). Oligonucleotide probes were derived from peptide sequences of p75 and used to screen a cDNA library constructed from the human melanoma cell line SK-MEL-19.…”
Section: Resultsmentioning
confidence: 99%
“…The pMT4 clone was isolated from mouse melanocytic cells (15). Originally pMT4 cDNA was thought to code for mouse tyrosinase, which maps to the mouse c (albino) locus.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it was shown that the mouse tyrosinase cDNA, pmcTyrl , encodes a protein possessing tyrosine hydroxylase activity, namely functional tyrosinase. The amino acid sequence deduced from the nucleotide sequence of pmcTyrl shows about 40% homology with the entire region of mouse tyrosinase deduced from pMT4 (Shibahara et al 1986). It is therefore conceivable that there may be at least two tyrosinase isozymes encoded by two distinct genes, and that the enzyme protein encoded by pMT4 may possess dopy oxidase activity instead of tyrosine hydroxylase activity.…”
mentioning
confidence: 92%
“…We have isolated a pigment cell-specific mouse cDNA, pMT4, and provided evidence that it encodes tyrosinase (Shibahara et al 1986). Recently, other groups have isolated and sequenced another cDNAs encoding mouse tyrosinase (Yamamoto et al 1987; Kwon et al 1988;Muller et al 1988) and a cDNA for human tyrosinase, Pmel 34 (Kwon et al 1987).…”
mentioning
confidence: 99%
“…Two were deduced from tyrosinase (17) and tyrosinase-related protein 1 (TRP-1; ref. 18). The sequences of the tyrosinase peptides were YYVSRDTLL (amino acids 128-136) and PYLEQASRI (amino acids 468-474).…”
mentioning
confidence: 99%